2021
DOI: 10.31298/sl.145.5-6.5
|View full text |Cite
|
Sign up to set email alerts
|

Prvi nalaz azijske pamučne štitaste uši Takahashia japonica u Hrvatskoj

Abstract: Azijska pamučna štitasta uš Takahashia japonica Cockerell (Hemiptera, Coccomorpha, Coccidae), vrsta je porijeklom iz Japana. U Europi je prvi put pronađena 2017. godine u Italiji te 2018. godine u Velikoj Britaniji. U ovom radu dajemo pregled prvog nalaza vrste T. japonica u Hrvatskoj. Prvi nalaz kukca T. japonica uočen je 2019. godine u Puli (Istarska županija, Hrvatska), a vrsta je determinirana u proljeće 2020 godine. Kako bi što učinkovitije prikupili terenske podatke, pokrenuli smo kampanju po načelu „gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…No official measures are in place. In 2019, T. japonica was found in Pula, Istrian County, Croatia, but was not identified until found again on Albizia julibrissim in May 2020 (Landeka et al, 2021). The Croatian NPPO confirmed that the pest is present with few occurrences, and no official measures to limit the spread of the pest are applied.…”
Section: Pest Distribution In the Eumentioning
confidence: 99%
See 3 more Smart Citations
“…No official measures are in place. In 2019, T. japonica was found in Pula, Istrian County, Croatia, but was not identified until found again on Albizia julibrissim in May 2020 (Landeka et al, 2021). The Croatian NPPO confirmed that the pest is present with few occurrences, and no official measures to limit the spread of the pest are applied.…”
Section: Pest Distribution In the Eumentioning
confidence: 99%
“…According to Landeka et al (2021), Limonta et al (2022), Malumphy et al (2019) and Tuffen et al (2019), the main symptoms of T. japonica infestation are:…”
Section: Symptomsmentioning
confidence: 99%
See 2 more Smart Citations